Taking Risks at the Table. From Regime to Valence - Ventura Bordenca , Ilaria (E|C, 2024)
The essay presented here discusses the semiotic problems about collective cohabitations by addressing a specific issue, that of dietary cohabitations, in particular the way in which restrictive dietary regimes and convivial situations, dietary regulatory principles and the social need to be together. The assumption is that dietary regimes and convivial situations are two different forms of being at the table, two configurations that presuppose different values at play: physical self-care, measure, on the one hand, and pleasure, play, on the other. In both cases, there are systems of rules. The question is how to fit them together by making them compatible. To understand this, we will analyse the communication of slimming diets through the different forms of textuality they usually rely on: in addition to advertisements, websites and blogs, nowadays various protocols make extensive use of social media and smartphone apps.